2011
DOI: 10.3384/ecp1105748
|View full text |Cite
|
Sign up to set email alerts
|

Scale Up of Laboratory Scale to Industrial Scale Biogas Plants

Abstract: Industrial biogas plants often do not operate in their optimum. To investigate limits of anaerobic digestion processes experiments are necessary. Economically it would be feasible to perform these tests at laboratory scale, if the tests could be transferred to industrial scale. This work presents a preliminary study, in which two different scales of laboratory digesters are compared and reproducibility of tests is investigated. Therefore, three identical glass digesters with a liquid volume of up to 22 liter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Very few studies [58][59][60][61][62][63] have been noted in the literature that investigates hydrodynamics in an anaerobic digester under both scale-up and scale-down conditions of an actual biogas plant anaerobic digester. It is noted that the observation of mixing in digesters under real conditions is complex and cost-intensive.…”
Section: Correlation Between Lab-scale and Large-scale Mixing In Anaerobic Digestersmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies [58][59][60][61][62][63] have been noted in the literature that investigates hydrodynamics in an anaerobic digester under both scale-up and scale-down conditions of an actual biogas plant anaerobic digester. It is noted that the observation of mixing in digesters under real conditions is complex and cost-intensive.…”
Section: Correlation Between Lab-scale and Large-scale Mixing In Anaerobic Digestersmentioning
confidence: 99%
“…The energy requirement may be improved by adjusting the mixing period and configuration. Frey et al [63] observed that the power usage for mixing declined by 50% by changing the agitator location without any mixing efficiency loss. Kress et al [47] observed an 85% reduction in electricity usage by increasing the resting time of the mixer.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…As an alternative, the methane production data from the high-throughput biomethane potential tests (BMP) [47] may be described using more simplistic kinetic models [48][49][50] and used to predict the effect of different pretreatment approaches on AD performance. It has been demonstrated in several studies that BMP results correlate well with methane production in continuously operated AD systems despite the presence of scaling effects and fluctuations in methane production [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the proposed technologies should be analysed in detail and adjusted to national and local requirements. Scientists and biogas plant owners struggle with these problems not only in Poland but also in other countries [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%